2022
DOI: 10.1364/ao.444610
|View full text |Cite
|
Sign up to set email alerts
|

Combining deep learning with SUPPOSe and compressed sensing for SNR-enhanced localization of overlapping emitters

Abstract: We present gSUPPOSe, a novel, to the best of our knowledge, gradient-based implementation of the SUPPOSe algorithm that we have developed for the localization of single emitters. We study the performance of gSUPPOSe and compressed sensing STORM (CS-STORM) on simulations of single-molecule localization microscopy (SMLM) images at different fluorophore densities and in a wide range of signal-to-noise ratio conditions. We also study the combination of these methods wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…BA averages these two effects, indicating a slightly better performance for a larger PSF than the exact one (note that the optimum value is at size +10 %), which may be due to the pixel size and low SNR of the images. These behaviours corresponds to the ones observed in [13], where a thorough analysis of the capabilities of SUP-POSe to localize single emitters within the PSF is presented.…”
Section: Validation With Simulated Imagessupporting
confidence: 72%
See 3 more Smart Citations
“…BA averages these two effects, indicating a slightly better performance for a larger PSF than the exact one (note that the optimum value is at size +10 %), which may be due to the pixel size and low SNR of the images. These behaviours corresponds to the ones observed in [13], where a thorough analysis of the capabilities of SUP-POSe to localize single emitters within the PSF is presented.…”
Section: Validation With Simulated Imagessupporting
confidence: 72%
“…There are some basic recommendations when applying SUPPOSe to experimental images. Despite being very robust against high-frequency noise, SUP-POSe solutions may be affected by low-frequency noise that introduces artifacts from overfitting [13]. In a previous work it was shown that it is possible to detect these artifacts by acquiring at least three images of the same region under working conditions, and then process them separately to compare the reconstructions [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fluorescence microscopy, each acquired sample is the result of a noise process acting on the convolution between an underlying object -an arrangement of fluorescent proteins tied to the things we want to see-with the microscope response function -known as Point Spread Function or PSF. SUPPOSe is a convolution-based algorithm for improving microscopy images that relies on representing the object under microscope as a SUPperposition of POint SourcEs with the same intensity [1][2][3][4][5][6][7][8]. By knowing the instrument Point-Spread Function (PSF) and the image formation model, the optimum position of these sources can be retrieved by iteratively solving an optimization problem that results in a description of the object with better resolution than the image itself.…”
Section: Introductionmentioning
confidence: 99%